Rancang Bangun Sistem Informasi Akuntansi (SIA) Kas Non-BOS Pada SMP Bahagia Yayasan Al Falah Rawamangun - Anisa Putri Isnaini; Hera Khairunnisa; Rochma Sudiati (Jurnal Akuntansi, Perpajakan dan Auditing, 2026)
This project aimed to design an Accounting Information System (AIS) for non-BOS cash receipts and disbursements at SMP Bahagia Yayasan Al Falah Rawamangun using Microsoft Excel integrated with Visual Basic for Applications (VBA). The system was developed using the Waterfall method through the requirement analysis, design, implementation, and verification stages. The findings showed that non-BOS cash management was still manual, cash disbursements were not systematically documented, and financial reporting was delivered verbally. The developed AIS automates transaction recording, generates general ledger, cash and bank, and cash balance reports, and includes a student payment management feature. System testing confirmed that all functions met user requirements. The system improves recording and reporting, increases the treasurer’s efficiency, and supports transparency and accountability in school financial management. However, it is limited to non-BOS cash management and has not been integrated with the BOS fund management system.